The diversification of banking. : papers and group discussons from the 35th International Banking Summer School held at St. Andrews University, Scotland, June, 1982 - Institute of Bankers in Scotland (Edinburgh : The Institute of Bankers in Scotland, 1982)
Diversification of banking is a collection of papers and group discussions from the 35th International Banking Summer School held at the St Andrews University, Scotland, June 1982. Some of the papers include: banking a perspective; the implication of technological change; the economies of retail banking in the future; financing the development of natural resources; control and supervision of banking; the competition for corporate and personal banking business; the international perspectives; and the human resources in banking.
lje 16/10/18
Loans
Keywords: Banking; Finance; Scotlant